EFFECT OF THE USE OF MEDICAL MASK WASTE AS AN INGREDIENT IN LASTON AC-BC MIXTURE TO THE VALUE OF STABILITY - bobby damara (Universitas Muhammadiyah Surabaya, 2023)
The construction of highway construction is experiencing a very rapid development , especially in Indonesia and it is undeniable that highways are a vital sector of economic development in developed countries, Realizing the importance of toll roads for logistics delivery, the government continued to speed up its construction starting in 2015(Afriyanto, Indriyati and Hardini, 2019). Until 2018, the toll road that has been built along 782 Km. Development continues to date, the government targets the construction of toll roads in 2019 along 1,070 Km. Total toll road construction later, during the reign of President Jokowi reached 1,852 Km (Ariswa, Andriani and Irawan, 2020)The COVID-19 pandemic is a very disturbing outbreak for Indonesian citizens and for the world since the beginning of the emergence of covid-19 in our country is required to adapt by implementing 3M (social distancing, wearing masks, and washing hands)(Wang et al., 2022), the use of masks has become mandatory in this pandemic masses and due to overload the use of masks, especially 3 ply medical masks made of water-absorbing materials such as cotton on the final layer then the middle layer as a filter is made of materials such as non-woven polypropylene and the outer layer is made of waterproof materials such as polyester, in accordance with WHO advice the use of masks is required as an effort to break the chain of the covid-19 virus so that it does not spread widely but As a result of the use of masks with a high amount , of course, there is an effect on the environment that masks cannot be decomposed properly by the soil because physically the masks have Plastic-like characters are plastic that takes a long time to decompose with soil(Dong et al., 2021).Seeing the problem of medical mask waste p there is this new normal era, we are required to always innovate in order to adapt to the Covid-19 pandemic, in line with the leadership of President Jokowidodo who carries the advancement of infrastructure in Indonesia, especially in the highway sector, this study aims to utilize medical mask waste as a hot asphalt mixture material (Asphalt Hotmix) by using the experimental method of using waste masks with a composition of 5%, 7% and 10% as a substitute for asphalt which is reviewed on asphalt stability